Pohl's Introduction to Physics Volume 2: Electrodynamics and Optics (Springer International Publishing, 2018)
This introductory textbook on experimental physics covers the fields of electrodynamics and optics. It is a new edition of one of the classic textbooks by Robert W. Pohl, written to accompany his famous lecture courses. It served generations of physics and other science majors, not only in his native Germany, and was for many years a standard textbook. Pohl's lucid and memorable style and his consistent use of vivid demonstration experiments made his textbooks unique in their time. This completely revised and updated modern edition attempts to retain his style and clarity in an up-to-date format. The accompanying videos document the original demonstration experiments and add many modern touches, bringing to life the numerous illustrations in the book and providing an instructive and motivating complement to the text. They are linked to the corresponding topics in the text and can be accessed directly online from the e-book version or downloaded to accompany the print version. The clear and structured presentation, always based on experimental demonstrations, gives a lively introduction to the main disciplines in classical physics, here electrodynamics and optics. Although this volume is, like its originals, relatively modest in length, the material it covers often exceeds what is expected of an introductory textbook. Thus the book is suitable not only for undergraduate students and their lecturers, but also for more advanced students and generally interested readers, including teachers at all levels.